The squad - Soontornvat, Christina; Cacao, Joanna; Soontornvat, Christina (New York : Graphix, an imprint of Scholastic, Inc., 2024)
As an 8th grader from a racially mixed family, Christina faces a new set of challenges, heartbreaks and triumphs.
Sequel to: The tryout.
The stakes have never been higher--Front cover.
Kirkus Review, October 2024
5-8
GN260L
Keywords: Best friends -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Cheerleading -- Comic books, strips, etc; Middle schools -- Comic books, strips, etc; Schools -- Comic books, strips, etc; Thai Americans -- Comic books, strips, etc; Iranian Americans -- Comic books, strips, etc; Best friends -- Fiction; Friendship -- Fiction; Cheerleading -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Thai Americans -- Fiction; Iranian Americans -- Fiction; Cheerleading -- Fiction; Thai Americans -- Fiction; School comics; Graphic novels; Comics (Graphic works)